Raman spectroscopy of carbon materials and their composites: Graphene, nanotubes and fibres - Li, Zheling; Deng, Libo; Kinloch, Ian A.; Young, Robert J. (Progress in materials science, 2023)
Raman spectroscopy is now an extremely important technique for the analysis of carbon-based materials. It is demonstrated how it can be used to give a unique insight into characterising many aspects of the microstructure of these materials, including orientation, number of layers, defects and doping, enabling standardisation and quality control. Graphene, as the building block of all sp2 carbon materials is used as the main example and it is demonstrated how the understanding of this material has facilitated the analysis of carbon nanotubes and fibres. It is also shown that the Raman bands shift during deformation and that these shifts are related through a universal calibration. It is demonstrated how these stress-induced Raman band shifts can be used to follow the deformation of the carbon-based materials and that this can be employed for the study of the interfacial micromechanics in model composite specimens. Finally the application of Raman spectroscopy to the characterisation of the structure and physical properties, both mechanical and thermal, of bulk carbon-based composites is described in detail. The application of Raman spectroscopy to the study of a broader range of materials and the potential for instrumental innovations to enable further extension of the technique are discussed briefly.